Envelope addressed to James Curtis Booth from the Assay Department, Mint of the United States at Philadelphia (1887)
James Curtis Booth (1810-1888) has noted on the envelope verso that the letter once contained by the envelope was sent by a Rev. Mr. Burch from the Seamen's Mission concerning the death of a female scholar.
Keywords: Booth, James Curtis, 1810-1888